Composite electron transport layer and preparation method and application thereof
By setting an organic metal salt transition layer between the C60 layer and the metal oxide layer of the perovskite solar cell, adjusting the water-metal ratio, the problem of water-metal ratio imbalance in the prior art is solved, and the carrier transmission efficiency and performance of perovskite solar cell are improved.
Patent Information
- Application Number
- CN202411969255.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
In existing perovskite solar cells, the water-metal ratio between C60 and the metal oxide layer is imbalanced, resulting in a mismatch of metal-water reactions at the interface, affecting battery performance and stability.
A transition layer of organometallic salt is arranged between the fullerene C60 layer and the metal oxide layer, and the water-metal ratio is adjusted to achieve a matching equilibrium state and reduce the decomposition of perovskite by water vapor.
By adjusting the water-metal ratio, the carrier transmission efficiency of the electron transport layer is improved, and the performance and stability of perovskite solar cells are improved.
Smart Images

Figure CN119816080A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells and relates to a composite electron transport layer and a preparation method and application thereof. Background Art
[0002] Perovskite solar cells have attracted widespread attention from academia and industry due to their many advantages such as adjustable band gap and low cost. At present, the highest photoelectric conversion efficiency of single-junction perovskite solar cells has increased from 3.8% in 2009 to 26.25% in 2023. The rapid development of perovskite solar cells is based on the improvement of the quality of perovskite materials themselves, and on the other hand, it also benefits from the development of efficient and stable interface transport layer preparation and its processing technology. However, the poor stability of perovskite itself and the interface transport layer has greatly hindered the commercialization process of perovskite solar cells. Therefore, the preparation of an efficient and stable interface transport layer is also an effective means to help improve the stability of perovskite solar cells.
[0003] In existing perovskite solar cells, metal oxide transport layer materials such as SnO2, TiO2, and NiO are widely used due to their low cost and stable performance. The electron transport layer (ETL) commonly used in current large-scale inverted perovskite solar modules is a combined transport layer of C60 and SnO2.
[0004] CN118880284A discloses a method for preparing a composite inorganic electron transport layer and a perovskite battery. It utilizes the self-limited growth characteristics of the ALD process to not only deposit a large-area uniform and dense non-polar electron transport layer film, but also first uses water and / or hydrogen peroxide vapor as an oxygen source to deposit a growth transition layer, and then uses oxygen and / or ozone as an oxygen source to deposit a growth main layer.
[0005] CN118870841A discloses a perovskite solar cell, which relates to the technical field of solar cells. According to an embodiment of the present application, the perovskite solar cell includes: an electron transport layer; a passivation layer, the passivation layer is arranged on one side of the electron transport layer; and a perovskite thin film layer, the perovskite thin film layer is arranged on the side of the passivation layer away from the electron transport layer.
[0006] The above schemes all use tin oxide and fullerene C 60 Composite electron transport layer, usually C before deposition of tin oxide 60 The film layer will be exposed to the air, and some water vapor will be adsorbed on the film surface, causing the reaction ratio of water and tin at the interface to change during the normal deposition of tin oxide, and the battery performance will decrease. Summary of the invention
[0007] The purpose of the present invention is to provide a composite electron transport layer and a preparation method and application thereof. 60 A layer of organic metal salt transition layer is set between the layer and the metal oxide layer to improve the fullerene C 60 The water-metal ratio between the electron transport layer and the metal oxide layer is increased, the carrier transport efficiency of the electron transport layer is improved, and the performance of the perovskite device is improved.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a composite electron transport layer, wherein the composite electron transport layer comprises fullerene C 60 layer, a metal oxide layer and a layer disposed on the fullerene C 60 An organic metal salt transition layer between the layer and the metal oxide layer;
[0010] Wherein, the metal oxide layer and the metal element in the organic metal salt transition layer are of the same type.
[0011] The present invention is a fullerene C in the electron transport layer 60 An organic metal salt transition layer is provided between the layer and the metal oxide layer to adjust the fullerene C 60 The ratio of water and metal elements between the layer and the metal oxide layer makes C 60 -The metal-water ratio at the metal oxide interface reaches a matched equilibrium state, reducing the decomposition effect of water vapor on the perovskite in the battery, thereby improving the performance of perovskite solar cells.
[0012] Preferably, the material of the organic metal salt transition layer includes TDMASn.
[0013] Preferably, the thickness of the organic metal salt transition layer is 0.1 nm to 0.5 nm, for example, 0.1 nm, 0.2 nm, 0.3 nm, 0.4 nm or 0.5 nm, etc., not limited to the listed values, other values not listed in the numerical range are also applicable, preferably 0.1 nm to 0.3 nm.
[0014] Preferably, the fullerene C 60 The thickness of the layer is 10 nm to 30 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm or 30 nm, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0015] Preferably, the material of the metal oxide layer includes tin oxide and / or zinc oxide, preferably tin oxide.
[0016] Preferably, the thickness of the metal oxide layer is 20 nm, for example, 10 nm, 15 nm, 20 nm, 25 nm or 30 nm, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0017] In a second aspect, the present invention provides a method for preparing the composite electron transport layer as described in the first aspect, the preparation method comprising the following steps:
[0018] (1) Deposition of fullerene C on a substrate 60 , forming fullerene C 60 layer;
[0019] (2) after the fullerene C60 layer is exposed, an organic metal salt is deposited to form an organic metal salt transition layer;
[0020] (3) Depositing a metal oxide layer on the organic metal salt transition layer to obtain the composite electron transport layer.
[0021] In the present invention, before the normal deposition of tin oxide, after being exposed to an environment with appropriate humidity for a period of time, an organic metal salt is first deposited with a source, and water is not deposited to form an organic metal salt transition layer, and then a tin oxide layer is deposited to change C 60 -The metal-water ratio at the metal oxide interface effectively reduces the decomposition of perovskite by water vapor and improves the stability of the battery. At the same time, the optimization at the interface increases the carrier transfer efficiency and improves the filling of the device.
[0022] Preferably, the substrate in step (1) comprises a perovskite active layer.
[0023] Preferably, the ambient humidity of the exposure treatment in step (2) is 20% to 50%, for example: 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc., preferably 20% to 40%, not limited to the listed values, other values not listed within the numerical range are also applicable.
[0024] Preferably, the exposure time of step (2) is 30s to 60s, for example, 30s, 35s, 40s, 50s or 60s, etc., not limited to the listed values, other values not listed within the numerical range are also applicable, preferably 30s to 50s.
[0025] In a third aspect, the present invention provides a perovskite solar cell, wherein the perovskite solar cell comprises the composite electron transport layer as described in the first aspect.
[0026] Preferably, the perovskite solar cell comprises a transparent conductive layer, a hole transport layer, a perovskite active layer, a composite electron transport layer and a top electrode layer which are stacked in sequence.
[0027] Preferably, the fullerene C of the composite electron transport layer 60 The layer is close to the perovskite active layer.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention is in fullerene C 60 A layer of organic metal salt transition layer is set between the layer and the metal oxide layer to improve the fullerene C 60 The water-metal ratio between the electron transport layer and the metal oxide layer is increased, the carrier transport efficiency of the electron transport layer is improved, and the performance of the perovskite device is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 1 is a schematic diagram of the structure of the composite electron transport layer in the perovskite solar cell described in Example 1, 1 is FTO transparent conductive glass, 2 is nickel oxide hole transport layer, 3 is Cs 0.15 FA 0.85 PbI3 perovskite light absorbing layer, 4 is fullerene C 60 layer, 5 is a TDMASn transition layer, 6 is a tin oxide layer, and 7 is a Cu top electrode layer 7. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0032] Example 1
[0033] This embodiment provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0034] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0035] (2) Exposure to fullerene C for 40 s in an environment with a humidity of 20% 60 TDMASn is deposited on the layer to form an organic metal salt transition layer with a thickness of 0.2 nm;
[0036] (3) A tin oxide layer with a thickness of 20 nm is deposited on the organic metal salt transition layer to obtain the composite electron transport layer.
[0037] The schematic diagram of the structure of the composite electron transport layer in the perovskite solar cell is as follows Figure 1 As shown, the perovskite solar cell comprises a FTO transparent conductive glass 1, a nickel oxide hole transport layer 2, and a Cs0.15 FA 0.85 PbI3 perovskite light absorbing layer 3, fullerene C 60 Layer 4, TDMASn transition layer 5, tin oxide layer 6 and Cu top electrode layer 7.
[0038] Example 2
[0039] This embodiment provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0040] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0041] (2) Exposure to 20% humidity for 50 s in fullerene C 60 TDMASn is deposited on the layer to form an organic metal salt transition layer with a thickness of 0.2 nm;
[0042] (3) A tin oxide layer with a thickness of 20 nm is deposited on the organic metal salt transition layer to obtain the composite electron transport layer.
[0043] Example 3
[0044] This embodiment provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0045] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0046] (2) Exposure to 40% humidity for 30 seconds in fullerene C 60 TDMASn is deposited on the layer to form an organic metal salt transition layer with a thickness of 0.2 nm;
[0047] (3) A tin oxide layer with a thickness of 20 nm is deposited on the organic metal salt transition layer to obtain the composite electron transport layer.
[0048] Example 4
[0049] This embodiment provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0050] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0051] (2) Exposure to fullerene C for 40 s in an environment with a humidity of 20% 60TDMASn is deposited on the layer to form an organic metal salt transition layer with a thickness of 0.1 nm;
[0052] (3) A tin oxide layer with a thickness of 20 nm is deposited on the organic metal salt transition layer to obtain the composite electron transport layer.
[0053] Example 5
[0054] This embodiment provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0055] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0056] (2) Exposure to fullerene C for 40 s in an environment with a humidity of 20% 60 TDMASn is deposited on the layer to form an organic metal salt transition layer with a thickness of 0.3 nm;
[0057] (3) A tin oxide layer with a thickness of 20 nm is deposited on the organic metal salt transition layer to obtain the composite electron transport layer.
[0058] Example 6
[0059] This embodiment provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0060] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0061] (2) Exposure to fullerene C for 40 s in an environment with a humidity of 20% 60 TDMASn is deposited on the layer to form an organic metal salt transition layer with a thickness of 0.5 nm;
[0062] (3) A tin oxide layer with a thickness of 20 nm is deposited on the organic metal salt transition layer to obtain the composite electron transport layer.
[0063] Example 7
[0064] This embodiment provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0065] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0066] (2) Exposure to 20% humidity for 80 seconds in fullerene C 60TDMASn is deposited on the layer to form an organic metal salt transition layer with a thickness of 0.2 nm;
[0067] (3) A tin oxide layer with a thickness of 20 nm is deposited on the organic metal salt transition layer to obtain the composite electron transport layer.
[0068] Example 8
[0069] This embodiment provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0070] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0071] (2) Exposure to 20% humidity for 20 seconds in fullerene C 60 TDMASn is deposited on the layer to form an organic metal salt transition layer with a thickness of 0.2 nm;
[0072] (3) A tin oxide layer with a thickness of 20 nm is deposited on the organic metal salt transition layer to obtain the composite electron transport layer.
[0073] Example 9
[0074] This embodiment provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0075] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0076] (2) Exposure to 10% humidity for 40 seconds in fullerene C 60 TDMASn is deposited on the layer to form an organic metal salt transition layer with a thickness of 0.2 nm;
[0077] (3) A tin oxide layer with a thickness of 20 nm is deposited on the organic metal salt transition layer to obtain the composite electron transport layer.
[0078] Example 10
[0079] This embodiment provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0080] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0081] (2) Exposure to 70% humidity for 30 seconds in fullerene C 60TDMASn is deposited on the layer to form an organic metal salt transition layer with a thickness of 0.2 nm;
[0082] (3) A tin oxide layer with a thickness of 20 nm is deposited on the organic metal salt transition layer to obtain the composite electron transport layer.
[0083] Comparative Example 1
[0084] This comparative example provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0085] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0086] (2) In fullerene C 60 A tin oxide layer with a thickness of 20 nm is deposited on the layer to obtain the composite electron transport layer.
[0087] Comparative Example 2
[0088] This comparative example provides a composite electron transport layer, and the preparation method of the composite electron transport layer is as follows:
[0089] (1) Deposition of fullerene C on a substrate 60 , forming a fullerene C with a thickness of 20nm 60 layer;
[0090] (2) Blow-drying Fullerene C 60 The water vapor on the layer, in the fullerene C 60 A tin oxide layer with a thickness of 20 nm is deposited on the layer to obtain the composite electron transport layer.
[0091] Performance Test:
[0092] The nickel oxide hole transport layer, Cs 0.15 FA 0.85 A PbI3 perovskite light absorbing layer was prepared, and an electron transport layer was prepared according to the methods described in the embodiment and the comparative example, and finally a Cu top electrode was deposited on the electron transport layer to obtain a perovskite solar cell (100 integrated perovskite solar cells). The perovskite solar cell was tested, and the short-circuit current Isc, open-circuit voltage Voc, fill factor FF and conversion efficiency Eff test results were recorded as shown in Table 1:
[0093] Table 1
[0094]
[0095]
[0096] As can be seen from Table 1, from Examples 1-5, the short-circuit current Isc of the perovskite solar cell made of the composite electron transport layer of the present invention can reach more than 1.6A, the open circuit voltage Voc can reach more than 103.65V, the fill factor FF can reach more than 0.72, and the conversion efficiency Eff can reach more than 16.58%.
[0097] By comparing Example 1 and Example 6, it can be seen that in the composite electron transport layer of the present invention, the thickness of the organic metal salt transition layer will affect its performance. When the thickness of the organic metal salt transition layer is controlled at 0.1nm to 0.3nm (due to the characteristics of the materials used, an organic metal salt transition layer below 0.1nm cannot be prepared), the performance of the composite electron transport layer is better. If the thickness of the organic metal salt transition layer is too large, the carrier transport process will be hindered.
[0098] By comparing Example 1 with Examples 7-8, it can be seen that during the preparation process of the composite electron transport layer of the present invention, the exposure time will affect its performance. When the exposure time is controlled within 30s to 60s, the performance of the composite electron transport layer is better. If the exposure time is too long, the water vapor adsorbed on the surface will increase, which will lead to the easy decomposition of the perovskite. If the exposure time is too short, it will lead to an excess of organic metal salts, which will also affect the transmission of its carriers.
[0099] By comparing Example 1 with Examples 9-10, it can be seen that during the preparation process of the composite electron transport layer of the present invention, the exposed ambient humidity will affect its performance. By controlling the exposure time to 30s to 60s, the performance of the composite electron transport layer is better. If the exposed ambient humidity is too high, the water vapor adsorbed on the surface will increase, which will lead to the easy decomposition of the perovskite. If the exposed ambient humidity is too low, it will lead to an excess of organic metal salts, which will also affect the transmission of its carriers.
[0100] By comparing Example 1 with Comparative Example 1, it can be seen that, before the normal deposition of tin oxide, the present invention first performs source deposition of organic metal salts without water deposition after being exposed to an environment with appropriate humidity for a period of time, to form an organic metal salt transition layer, and then deposits a tin oxide layer, thereby changing C 60 -The metal-water ratio at the metal oxide interface effectively reduces the decomposition of perovskite by water vapor and improves the stability of the battery. At the same time, the optimization at the interface increases the carrier transfer efficiency and improves the filling of the device.
[0101] From the comparison between Example 1 and Comparative Example 2, it can be seen that ordinary drying cannot completely remove the water vapor in the film layer, and inevitably there will be residues. Therefore, the organic metal salt transition layer added in the present invention can not only save the drying process, but also further improve the performance.
[0102] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite electron transport layer, characterized in that: The composite electron transport layer includes fullerene C 60 layer, a metal oxide layer and a layer disposed on the fullerene C 60 An organic metal salt transition layer between the layer and the metal oxide layer; Wherein, the metal oxide layer and the metal element in the organic metal salt transition layer are of the same type.
2. The composite electron transport layer according to claim 1, characterized in that The material of the organic metal salt transition layer includes TDMASn; Preferably, the thickness of the organic metal salt transition layer is 0.1 nm to 0.5 nm, preferably 0.1 nm to 0.3 nm.
3. The composite electron transport layer according to claim 1, characterized in that The fullerene C 60 The thickness of the layer is 10 nm to 30 nm.
4. The composite electron transport layer according to any one of claims 1 to 3, characterized in that: The material of the metal oxide layer includes tin oxide and / or titanium oxide, preferably tin oxide; Preferably, the thickness of the metal oxide layer is 10 nm to 30 nm.
5. A method for preparing a composite electron transport layer according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) Deposition of fullerene C on a substrate 60 , forming fullerene C 60 layer; (2) after the fullerene C60 layer is exposed, an organic metal salt is deposited to form an organic metal salt transition layer; (3) Depositing a metal oxide layer on the organic metal salt transition layer to obtain the composite electron transport layer.
6. The preparation method according to claim 5, characterized in that: The substrate in step (1) includes a perovskite active layer.
7. The preparation method according to claim 5 or 6, characterized in that: The ambient humidity of the exposure treatment in step (2) is 20% to 50%, preferably 20% to 40%.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The exposure treatment time in step (2) is 30s to 60s, preferably 30s to 50s.
9. A perovskite solar cell, characterized in that: The perovskite solar cell comprises the composite electron transport layer according to any one of claims 1 to 4.
10. The perovskite solar cell according to claim 9, characterized in that: The perovskite solar cell comprises a transparent conductive layer, a hole transport layer, a perovskite active layer, a composite electron transport layer and a top electrode layer which are stacked in sequence; Preferably, the fullerene C of the composite electron transport layer 60 The layer is close to the perovskite active layer.
Citation Information
Patent Citations
Preparation method of composite inorganic electron transport layer and perovskite cell
CN118880284A